Niche partitioning in arbuscular mycorrhizal communities in temperate grasslands: a lesson from adjacent serpentine and nonserpentine habitats - Kohout, Petr; Doubková, Pavla; Bahram, Mohammad; Suda, Jan; Tedersoo, Leho; Voříšková, Jana; Sudová, Radka (Molecular ecology, 2015)
Arbuscular mycorrhizal fungi (AMF) represent an important soil microbial group playing a fundamental role in many terrestrial ecosystems. We explored the effects of deterministic (soil characteristics, host plant life stage, neighbouring plant communities) and stochastic processes on AMF colonization, richness and community composition in roots of Knautia arvensis (Dipsacaceae) plants from three serpentine grasslands and adjacent nonserpentine sites. Methodically, the study was based on 454-sequencing of the ITS region of rDNA. In total, we detected 81 molecular taxonomical operational units (MOTUs) belonging to the Glomeromycota. Serpentine character of the site negatively influenced AMF root colonization, similarly as higher Fe concentration. AMF MOTUs richness linearly increased along a pH gradient from 3.5 to 5.8. Contrary, K and Cr soil concentration had a negative influence on AMF MOTUs richness. We also detected a strong relation between neighbouring plant community composition and AMF MOTUs richness. Although spatial distance between the sampled sites (c. 0.3-3 km) contributed to structuring AMF communities in K. arvensis roots, environmental parameters were key factors in this respect. In particular, the composition of AMF communities was shaped by the complex of serpentine conditions, pH and available soil Ni concentration. The composition of AMF communities was also dependent on host plant life stage (vegetative vs. generative). Our study supports the dominance of deterministic factors in structuring AMF communities in heterogeneous environment composed of an edaphic mosaic of serpentine and nonserpentine soils.
Keywords: Mycorrhizae; environmental DNA; pastviny; Soil; DNA, Ribosomal Spacer; fungi; Ecosystem; kořeny rostlin; Grassland; community ecology; fylogeneze; DNA, Fungal; mykorhiza; ekosystém; DNA fungální; půdní mikrobiologie; Soil Microbiology; Dipsacaceae; DNA barcoding; Plant Roots; půda; microbial biology; Phylogeny; mezerníky ribozomální DNA